2018
DOI: 10.1007/s10068-018-0325-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carica papaya and Cucumis melo seed oils on the soybean oil stability

Abstract: This study aimed to evaluate the oils of soybean (S), papaya (Pa) and melon (Me) seeds and compounds oils SPa (80:20 w/w); SMe (80:20 w/w); and SPaMe (60:20:20 w/w/w) subjected to thermoxidation. Compound oils showed lower percentages of free fatty acids in relation to others, after 20 h. With the heating process, there was an increase in the quantity of saturated and monounsaturated acids. The quantity of carotenoids decreased, except in papaya seed oil that presented significant amount of carotenoids in 20 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Soybean tocopherols were rich in γ-tocopherol (>66 %), whereas δ-tocopherol was >21% and α-tocopherol was 11%. Interestingly, α-tocopherol accounted for 100% of the total tocopherols in avocado oils [50,51].…”
Section: Main Components Of Asumentioning
confidence: 99%
“…Soybean tocopherols were rich in γ-tocopherol (>66 %), whereas δ-tocopherol was >21% and α-tocopherol was 11%. Interestingly, α-tocopherol accounted for 100% of the total tocopherols in avocado oils [50,51].…”
Section: Main Components Of Asumentioning
confidence: 99%
“…Casarotti and Jorge (2012) by the thermoxidation of the G. max oil at 180 °C/20 h and S/V of 0.4/cm obtained results from 1.38% to 33.16% of polar compounds. Veronezi and Jorge (2018) formulated mixtures of G. max, C. papaya and C. melo oils in different proportions and subjected them to thermoxidation. The oil blends showed lower percentages of total polar compounds, greater oxidative stability, in addition to retaining tocopherols better than pure oils, in 20 h of heating.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, variable ratios were used for oil blend formulations. It has been reported that soybean oil was added with 20% papaya oil, 20% melon oil, or with equal proportions of up to 40% for both in order to enhance the thermo-oxidation stability (Veronezi and Jorge, 2018). The same proportions and combinations were studied by Olagunju et al (2022) using sesame and cashew nut oils.…”
Section: Binary Blends Of Soybean Oil With Cold-pressed Oilsmentioning
confidence: 99%
“…Soybean oil frying showed an increased formation of primary oxidation compounds and a decrease in oxidative stability. The addition of melon or papaya oil to soybean oil (20:80) showed amelioration in physicochemical parameters and increased the nutritional value and stability of soybean oil (Veronezi and Jorge, 2018). The formulation of frying oil by blending of soybean oil with sesame oil at a ratio of 60:40 allowed reducing its viscosity, making it desirable for cooking purposes, and offering protection from acidity development by 10% (Garg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%